High-Quality Genome Assembly of Fusarium oxysporum f. sp. lini - Krasnov, George S.; Pushkova, Elena N.; Novakovskiy, Roman O.; Kudryavtseva, Ludmila P.; Rozhmina, Tatiana A.; Dvorianinova, Ekaterina M.; Povkhova, Liubov V.; Kudryavtseva, Anna V.; Dmitriev, Alexey A.; Melnikova, Nataliya V. (Frontiers in Genetics, 2020)
In the present work, a highly pathogenic isolate of Fusarium oxysporum f. sp. lini, which is the most harmful pathogen affecting flax (Linum usitatissimum L.), was sequenced for the first time. To achieve a high-quality genome assembly, we used the combination of two sequencing platforms – Oxford Nanopore Technologies (MinION system) with long noisy reads and Illumina (HiSeq 2500 instrument) with short accurate reads. Given the quality of DNA is crucial for Nanopore sequencing, we developed the protocol for extraction of pure high-molecular-weight DNA from fungi. Sequencing of DNA extracted using this protocol allowed us to obtain about 85x genome coverage with long (N50=29 kb) MinION reads and 30x coverage with 2x250 bp HiSeq reads. Several tools were developed for genome assembly from sequencing data; however, they provide different results depending on genome complexity, sequencing data volume, read length and quality. We benchmarked the most requested assemblers (Canu, Flye, Shasta, wtdbg2, MaSuRCA), Nanopore polishers (Medaka and Racon), and Illumina polishers (Pilon and POLCA) on our sequencing data. The assembly performed with Canu and polished with Medaka and POLCA was considered the most full and accurate. After further elimination of redundant contigs using Purge Haplotigs, we achieved a high-quality genome of F. oxysporum f. sp. lini with a total length of 59 Mb, N50 of 3.3 Mb, and 99.5% completeness according to BUSCO. We also obtained a complete circular mitochondrial genome with a length of 38.7 kb. The achieved assembly expands studies on F. oxysporum and plant-pathogen interaction in flax.